Creation of Tissue-Engineered Urethras for Large Urethral Defect Repair in a Rabbit Experimental Model - Amesty, Maria Virginia; Chamorro, Clara Ibel; López-Pereira, Pedro; Martínez-Urrutia, María José; Sanz, Beatriz; Rivas, Susana; Lobato, Roberto; Fossum, Magdalena (Frontiers in Pediatrics, 2021)
Introduction: Tissue engineering is a potential source of urethral substitutes to treat severe urethral defects. Our aim was to create tissue-engineered urethras by harvesting autologous cells obtained by bladder washes and then using these cells to create a neourethra in a chronic large urethral defect in a rabbit model. Methods: A large urethral defect was first created in male New Zealand rabbits by resecting an elliptic defect (70 mm2) in the ventral penile urethra and then letting it settle down as a chronic defect for 5–6 weeks. Urothelial cells were harvested noninvasively by washing the bladder with saline and isolating urothelial cells. Neourethras were created by seeding urothelial cells on a commercially available decellularized intestinal submucosa matrix (Biodesign® Cook-Biotech®). Twenty-two rabbits were divided into three groups. Group-A (n = 2) is a control group (urethral defect unrepaired). Group-B (n = 10) and group-C (n = 10) underwent on-lay urethroplasty, with unseeded matrix (group-B) and urothelial cell-seeded matrix (group-C). Macroscopic appearance, radiology, and histology were assessed. Results: The chronic large urethral defect model was successfully created. Stratified urothelial cultures attached to the matrix were obtained. All group-A rabbits kept the urethral defect size unchanged (70 ± 2.5 mm2). All group-B rabbits presented urethroplasty dehiscence, with a median defect of 61 mm2 (range 34–70). In group-C, five presented complete correction and five almost total correction with fistula, with a median defect of 0.3 mm2 (range 0–12.5), demonstrating a significant better result (p = 7.85 × 10−5). Urethrography showed more fistulas in group-B (10/10, versus 5/10 in group-C) (p = 0.04). No strictures were found in any of the groups. Group-B histology identified the absence of ventral urethra in unrepaired areas, with squamous cell metaplasia in the edges toward the defect. In group-C repaired areas, ventral multilayer urothelium was identified with cells staining for urothelial cell marker cytokeratin-7. Conclusions: The importance of this study is that we used a chronic large urethral defect animal model and clearly found that cell-seeded transplants were superior to nonseeded. In addition, bladder washing was a feasible method for harvesting viable autologous cells in a noninvasive way. There is a place for considering tissue-engineered transplants in the surgical armamentarium for treating complex urethral defects and hypospadias cases.